2012
DOI: 10.5144/0256-4947.2012.513
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus in the western region of Saudi Arabia: prevalence and antibiotic susceptibility pattern

Abstract: BACKGROUND AND OBJECTIVESMethicillin-resistant Staphylococcus aureus (MRSA) emerged in 1960 and was a problem confined largely to the healthcare setting, or hospital-associated MRSA (HA-MRSA). In the 1990s, community-associated MRSA (CA-MRSA) infections appeared. In Saudi Arabia, the prevalence of MRSA has increased in the past ten years and severe community-acquired infection has been reported. Our objective was to investigate the prevalence of MRSA and their antibiotic susceptibilities in the western region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 18 publications
6
30
2
Order By: Relevance
“…However, their study comprises both Saudi and non-Saudi nationals while the ICU isolates in the present study were from Saudi nationals only as there were no available data for non-Saudis in this region at the time of the study. Also, similar to the report in the present investigation are those from a previous report (El-Amin and Faidah, 2012) in which there was a higher number of ICU males than females. This therefore indicates that there would be variations in different hospitals, within a country as well as around different regions of the world.…”
Section: Discussionsupporting
confidence: 92%
“…However, their study comprises both Saudi and non-Saudi nationals while the ICU isolates in the present study were from Saudi nationals only as there were no available data for non-Saudis in this region at the time of the study. Also, similar to the report in the present investigation are those from a previous report (El-Amin and Faidah, 2012) in which there was a higher number of ICU males than females. This therefore indicates that there would be variations in different hospitals, within a country as well as around different regions of the world.…”
Section: Discussionsupporting
confidence: 92%
“…Distribution of multidrug‐resistant Staphylococcus aureus and/or MRSA in the Kingdom is widely reported, and the incidence of a different type of MRSA was found to be especially higher in the Riyadh region . These previously published studies and the study presented here strongly suggest that camel milk serves as an important reservoir and carrier of such pathogens.…”
Section: Resultssupporting
confidence: 71%
“…Other study demonstrated Most isolates were from wound sites (71%) however in our case most isolate were from eye infection [10] another similar study shows MRSA was isolated in 39.5% of the specimens. The prevalence of MRSA was highest among patients who were 56 years old or older (52.2%) [11]. As compare to our study in which the young patients were more susceptible.…”
Section: Discussioncontrasting
confidence: 48%